Exploring the feasibility of smartglass facilitated remote supervision in the emergency department: A simulation study. (13th December 2022) - McTavish, Arthur; Larsen, Peter; Rogan, Alice; Carlin, Emma; Lynch, Matthew; Peckler, Brad
Abstract: Objective: Smartglasses are a wearable computer technology that has potential to facilitate remote supervision to junior doctors working in different clinical settings. The present study aimed to explore the feasibility of smartglass technology to enable remote supervision of junior clinicians by senior clinicians during emergency simulation scenarios. Methods: This was a feasibility simulation study using high‐fidelity mannequins and standardised patients. Trainee interns (TIs) and supervising clinicians (SCs) were invited to participate in two scenarios: a trauma case and a stroke case. There was a pre‐sim questionnaire. The TI wore the smartglasses in a simulated ED bay and performed patient assessment and management. Remote supervision was provided by the SC via a livestream on a remote computer. Upon completion, participants completed a survey regarding their experience comprising of Likert scale and free‐text questions. Results: Fifteen TIs and 19 SCs participated. In general feedback from TIs and SCs was positive. TIs were able to identify and treat the key diagnostic problems set during the scenarios. Free‐text survey responses provided specific feedback about what did and did not work when using the glasses. Conclusion: The present study demonstrates that smartglasses facilitated remote assistance has promise as an emergent technology and warrants further investigation in simulated and non‐simulated environments.